The New Metropolitan Police of Buenos Aires: Officers' Shared Perceptions on Community Policing and Organizational Practices. Issue 3 (17th February 2018) - Colvin, Roddrick
ABSTRACT: This exploratory research surveys police officers of the city of Buenos Aires who have joined the metropolitan police force. Specifically, it examines the officers' perceptions of community policing, reasons for joining the forces, and their beliefs concerning the integration of female police officers. Police officers reported solid knowledge about community policing and their role as its instruments. They expressed some doubt that the values of community policing are permeating throughout the organization, and that there was not enough time for officers to actually engage communities. The leadership of the department should focus efforts to ensure that community policing values are instilled throughout the organization, and providing officers with the time needed to develop community relations with the public.